Galectin-7 Impairs Placentation and Causes Preeclampsia Features in Mice. Issue 4 (October 2020) - Menkhorst, Ellen; Zhou, Wei; Santos, Leilani L.; Delforce, Sarah; So, Teresa; Rainczuk, Kate; Loke, Hannah; Syngelaki, Argyro; Varshney, Swati; Williamson, Nicholas; Pringle, Kirsty; Young, Morag J.; et al.
Abstract : Preeclampsia is a serious pregnancy-induced disorder unique to humans. The etiology of preeclampsia is poorly understood; however, poor placental formation is thought causal. Galectin-7 is produced by trophoblast and is elevated in first-trimester serum of women who subsequently develop preeclampsia. We hypothesized that elevated placental galectin-7 may be causative of preeclampsia. Here, we demonstrated increased galectin-7 production in chorionic villous samples from women who subsequently develop preterm preeclampsia compared with uncomplicated pregnancies. In vitro, galectin-7 impaired human first-trimester trophoblast outgrowth, increased placental production of the antiangiogenic sFlt-1 splice variant, sFlt-1-e15a, and reduced placental production and secretion of ADAM12 (a disintegrin and metalloproteinase12) and angiotensinogen. In vivo, galectin-7 administration (E8–E12) to pregnant mice caused elevated systolic blood pressure, albuminuria, impaired placentation (reduced labyrinth vascular branching, impaired decidual spiral artery remodeling, and a proinflammatory placental state demonstrated by elevated IL1β, IL6 and reduced IL10), and dysregulated expression of renin-angiotensin system components in the placenta, decidua, and kidney, including angiotensinogen, prorenin, and the angiotensin II type 1 receptor. Collectively, this study demonstrates that elevated galectin-7 during placental formation contributes to abnormal placentation and suggests that it leads to the development of preeclampsia via altering placental production of sFlt-1 and renin-angiotensin system components. Targeting galectin-7 may be a new treatment option for preeclampsia. Abstract : Supplemental Digital Content is available in the text.